The new woman in Uzbekistan : Islam, modernity, and unveiling under communism - Kamp, Marianne (Jackson School publications in international studies., 2006)
"This groundbreaking work in women's history explores the lives of Uzbek women, in their own voices and words, before and after the Russian Revolution of 1917. Drawing upon their oral histories and writings, Marianne Kamp reexamines the Soviet Hujum, the 1927 campaign in Soviet Central Asia to encourage mass unveiling as a path to social and intellectual "liberation." This examination of changing Uzbek ideas about women in the early twentieth century reveals the complexities of a volatile time: why some Uzbek women chose to unveil, why many were forcibly unveiled, why a campaign for unveiling triggered massive violence against women, and how the national memory of this pivotal event remains contested today."--Jacket